Criminal Justice System of Children in The Law Number 11 of 2012 (Restorative Justice) - Ansori Ansori (Universitas Muhammadiyah Sidoarjo, 2014)
The future of the children will determine the future of the nation. The increasing problem of juvenile delinquency in this globalization and information technology era, requires the state to give more attention to the child's future. Application of the criminal justice system for children in Indonesia is as stipulated in Law Number 3 of 1997 potentially detrimental to the child's interests. In practice, the judicial system had many problems, among them is a violation of the rights of children, such as: physical and psychological violence, as well as deprivation of the right to education and welfare. It happened because the juvenile justice system is against to national and international regulations on the protection of children’s rights. Besides that, theory of punishment for the juvenile delinquency still refers to the concept of retribution for the crimes. This concept is not very useful for the development of the child, so the concept need to be repaired with the concept of restorative justice. With this concept, the criminal justice system for the juvenile delinquency, leads to the restoration of the state and the settlement pattern, involving the perpetrator, the victim, their families and engage with the community. This is done with consideration for the protection of children against the law. Whereas in line with this spirit of the restorative justice, it gives birth to the Law No. 11 of 2012 on The Criminal Justice System of Children.